Photoprotective strategies in the motile cryptophyte alga Rhodomonas salina-role of non-photochemical quenching, ions, photoinhibition, and cell motility - Kaňa, Radek; Kotabová, Eva; Šedivá, Barbora; Kuthanová Trsková, Eliška (Folia microbiologica, 2019)
We explored photoprotective strategies in a cryptophyte alga Rhodomonas salina. This cryptophytic alga represents phototrophs where chlorophyll a/c antennas in thylakoids are combined with additional light-harvesting system formed by phycobiliproteins in the chloroplast lumen. The fastest response to excessive irradiation is induction of non-photochemical quenching (NPQ). The maximal NPQ appears already after 20 s of excessive irradiation. This initial phase of NPQ is sensitive to Ca2+ channel inhibitor (diltiazem) and disappears, also, in the presence of non-actin, an ionophore for monovalent cations. The prolonged exposure to high light of R. salina cells causes photoinhibition of photosystem II (PSII) that can be further enhanced when Ca2+ fluxes are inhibited by diltiazem. The light-induced reduction in PSII photochemical activity is smaller when compared with immotile diatom Phaeodactylum tricornutum. We explain this as a result of their different photoprotective strategies. Besides the protective role of NPQ, the motile R. salina also minimizes high light exposure by increased cell velocity by almost 25% percent (25% from 82 to 104 μm/s). We suggest that motility of algal cells might have a photoprotective role at high light because algal cell rotation around longitudinal axes changes continual irradiation to periodically fluctuating light.
Keywords: fotosystém II (proteinový komplex); Cryptophyta; chlorofyl a; Calcium; Light; Photosystem II Protein Complex; Chlorophyll; vápník; Chlorophyll A; Cell Movement; světlo; pohyb buněk; chlorofyl